# Solve the Following Quadratic Equation by Factorization 3x2-2√6x+2=0

By Mohit Uniyal|Updated : May 24th, 2023

Solve the following quadratic equation by factorization 3x2-2√6x+2=0

Given equation: 3x2-2√6x + 2 = 0

To solve this equation by factorization, we can follow these steps:

• Step 1: Identify the coefficients of the equation: a = 3, b = -2√6, and c = 2
• Step 2: Factor out any common factor among the terms, if possible.
• Step 3: Rewrite the middle term (bx) by splitting it into two terms such that their coefficients multiply to give ac, the product of the coefficients of the quadratic equation.
• Step 4: Rewrite the middle term using the numbers found in Step 3.
• Step 5: Group the terms in pairs and factor out the common factors.
• Step 6: Factor out the common binomial factor.
• Step 7: Set each factor equal to zero and solve for the desired answer.

## Solve the Following Quadratic Equation by Factorization 3x2-2√6x+2=0

Solution:

Rewrite the equation:

3x^2 - 2√6x + 2 = 0

3x^2 - √6x - √6x + 2 = 0

Finding out the common term:

√3x(√3x-√2) - √2 (√3x-√2) = 0

(√3x - √2)^2 = 0

On solving for for x, we will get

x = ±√(2/3)

So the correct solutios are: x = √(2/3) and x = -√(2/3)

## On Solving the Following Quadratic Equation by Factorization 3x2-2√6x+2=0, we get x = √(2/3) and x = -√(2/3)

Similar Questions: